2017
DOI: 10.1016/j.electacta.2017.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Mechanism of Ferrocene-Based Redox Molecules in Thin Film Membrane Electrodes

Abstract: 2 GRAPHICAL ABSTRACTCartoon illustrating NaCl permeation through water nanodroplets and Cl -exchange at the membrane/sample interface, both of which create an environment to enable the formation of FeCln 3-n complexes, leading to a non-reversibility in the redox chemistry of the membrane. RESEARCH HIGHLIGHTS electrochemistry of ferrocene derivatives in polymeric membranes  role of chloride on the irreversible oxidation of ferrocene in thin film membranes  synchrotron radiation study of chloride on the ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Figure a presents the observed SR‐VBS data. Importantly, these results are consistent with the notion that, at the buried interface, the membrane film comprises near to pure oxidation products of EtFc + Cl − and/or (EtFc + ) n‐3 FeCl n 3−n ion association complexes arising from the nucleophilic attack of Cl − as illustrated in a previous work , noting that previous Fe 2p NEXAFS spectroscopic evidence , not the present SR‐VBS data, provided evidence for the formation of Fe 3+ associated with oxidation of EtFc to EtFc + . Here, the SR‐VBS spectra at 13 to 20 min of Ar sputtering or depths of 156 to 240 nm (buried interface) correspond to the presence of strong levels of Fc and the gradient from the membrane surface to the buried interface reveals Fe 3d states at 2–3 eV (although Fe 2+ and Fe 3+ have 3d 6 and 3d 5 electron configurations respectively, such subtle changes in the Fe 3d DOS were not discernable from the convolution of PMMA‐PDMA SR‐VBS spectral features) together with C 2p π bonding states in Fc aromatic moieties at approximately 6–10 eV and C 2 s from EtFc at 12–13 eV .…”
Section: Methodsmentioning
confidence: 96%
See 4 more Smart Citations
“…Figure a presents the observed SR‐VBS data. Importantly, these results are consistent with the notion that, at the buried interface, the membrane film comprises near to pure oxidation products of EtFc + Cl − and/or (EtFc + ) n‐3 FeCl n 3−n ion association complexes arising from the nucleophilic attack of Cl − as illustrated in a previous work , noting that previous Fe 2p NEXAFS spectroscopic evidence , not the present SR‐VBS data, provided evidence for the formation of Fe 3+ associated with oxidation of EtFc to EtFc + . Here, the SR‐VBS spectra at 13 to 20 min of Ar sputtering or depths of 156 to 240 nm (buried interface) correspond to the presence of strong levels of Fc and the gradient from the membrane surface to the buried interface reveals Fe 3d states at 2–3 eV (although Fe 2+ and Fe 3+ have 3d 6 and 3d 5 electron configurations respectively, such subtle changes in the Fe 3d DOS were not discernable from the convolution of PMMA‐PDMA SR‐VBS spectral features) together with C 2p π bonding states in Fc aromatic moieties at approximately 6–10 eV and C 2 s from EtFc at 12–13 eV .…”
Section: Methodsmentioning
confidence: 96%
“…Very recently, it has been shown that the Cl − ‐degraded reaction product may irreversibly block the available Fc in the membrane to be oxidized, resulting in loss of the electrochemical signal . While this effect is drastic with chloride ions, where there is a gradual conversion of EtFc to EtFc + to irreversible FeCl n 3−n complexes after continuous CV cycling, it is gradual or imperceptible with larger anions (i. e. ClO 4 − , PF 6 − or organic anions).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations